Generality, continuity, and change in offending - Paternoster, Raymond (Journal of quantitative criminology, 1997)
A number of criminological theories make either implicit or explicit predictions about the empirical relationship between prior and future offending behavior. Some argue that time-stable characteristics such as criminal propensity should account for any positive correlation between past and future criminal behavior for all individuals. Others contend that the positive association between offending behavior at different points in time are partly causal and partly spurious. Still others anticipate that different patterns will emerge for different groups (distinguished by their ciminal propensity) of individuals. Using a longitudinal data set comprised of 848 training school releasees, we test various hypotheses emanating from these different theoretical perspectives. The results indicate that (1) both stability and change have causal implications for one's offending behavior and (2) with but one exception, these effects do not vary between high and low criminal propensity groups.